2005
DOI: 10.1603/0022-0493-98.2.509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy and Nonrepellency of Indoxacarb and Fipronil-Treated Soil at Various Concentrations and Thicknesses Against Two Subterranean Termites (Isoptera: Rhinotermitidae)

Abstract: The efficacy and nonrepellency of indoxacarb (150 SC, 150 g [AI]/liter) and fipronil (Termidor SC, 9.1% [Al]) against field-collected eastern subterranean termite, Reticulitermes flavipes (Kollar), and the Formosan subterranean termite, Coptotermes formosanus Shiraki, were evaluated for mortality and penetration into treated soil in laboratory glass tube bioassays. Both insecticides were tested at five concentrations (0, 1, 10, 50, and 100 ppm) and two thicknesses (20 and 50 mm) of treated soil. Indoxacarb cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Dose dependence was also shown in a previous study when varying levels of mortality and speed of death of C. formosanus and R. flavipes were observed over several concentrations of indoxacarb from 10 to 100 mg kg −1 . 18 Shelton and Grace 13 observed a similar phenomenon when C. formosanus donors were exposed to fipronil-or imidacloprid-treated sand (0.1 g AI kg −1 ) for 1 h and placed with recipients at a ratio 1:19. After a 15day interaction, the mean donor mortality was 97.8 or 100%, while the recipient mortality was 38.6 or 61.5%, respectively.…”
Section: Results and Discussion 31 Effects Of Dosementioning
confidence: 81%
See 2 more Smart Citations
“…Dose dependence was also shown in a previous study when varying levels of mortality and speed of death of C. formosanus and R. flavipes were observed over several concentrations of indoxacarb from 10 to 100 mg kg −1 . 18 Shelton and Grace 13 observed a similar phenomenon when C. formosanus donors were exposed to fipronil-or imidacloprid-treated sand (0.1 g AI kg −1 ) for 1 h and placed with recipients at a ratio 1:19. After a 15day interaction, the mean donor mortality was 97.8 or 100%, while the recipient mortality was 38.6 or 61.5%, respectively.…”
Section: Results and Discussion 31 Effects Of Dosementioning
confidence: 81%
“…A previous study of toxicity and barrier efficacy showed that a soil barrier (2 cm) containing 50-100 mg kg −1 indoxacarb killed all tested C. formosanus termites within 21 days and allowed a free and complete penetration of the soil barrier. 18 Although both studies tested groups of termites in laboratory conditions, the results indicate that indoxacarb could be a good candidate as soil insecticide against subterranean termites. Currently, trials are under way to evaluate the effectiveness of indoxacarb for subterranean termite control under field conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Reticulitermes flavipes were collected from Auburn University campus and C. formosanus from the city of Opelika, Lee County, Alabama in June 2008. The collections were maintained in plastic boxes with moistened corrugated cardboard rolls as food at 24 ± 1 • C and 80% ± 3% RH and were tested within 3 days of collection (Hu, 2005).…”
Section: Termitesmentioning
confidence: 99%
“…Thiacloprid selectively acts on the insect nervous system as an agonist of the nicotinic acetylcholine receptor (nAChR) [12]. Indoxacarb is a broad-spectrum, contact, low risk pesticide with low mammalian toxicity and a benign profile for avian and aquatic toxicity [13][14][15][16][17][18]. It affects insects from direct exposure to spray droplets and through ingestion of treated foliage or fruit.…”
Section: Introductionmentioning
confidence: 99%